2010
DOI: 10.3390/sym2020541
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry and Steroid Hormones: A Review

Abstract: Fluctuating asymmetry (FA) represents random, minor deviations from perfect symmetry in paired traits. Because the development of the left and right sides of a paired trait is presumably controlled by an identical set of genetic instructions, these small imperfections are considered to reflect genetic and environmental perturbations experienced during ontogeny. The current paper aims to identify possible neuroendocrine mechanisms, namely the actions of steroid hormones that may impact the development of asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 88 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…Fink and colleagues [126] found a significant correlation between prenatal testosterone level (low second-to-fourth digit ratio) and high facial asymmetry in males, but not females. These findings, however, are controversial [127].…”
Section: Sex Differencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Fink and colleagues [126] found a significant correlation between prenatal testosterone level (low second-to-fourth digit ratio) and high facial asymmetry in males, but not females. These findings, however, are controversial [127].…”
Section: Sex Differencesmentioning
confidence: 98%
“…Stressors operate through the hypothalamic-pituitary-adrenal axis [127], which acts in part as a link between the nervous system and the immune system. Under normally stressful conditions, corticotropin releasing hormone stimulates the release of adrenocorticotropic hormone, which stimulates the adrenal gland to release cortisol (a corticoid hormone).…”
Section: Stressorsmentioning
confidence: 99%
“…Consequently there is no strong correlation between asymmetry patterns and androgen levels among studied populations. Nevertheless a trend that higher androgen levels are associated with decreased asymmetry can be described for !Kung San males but only partly for Kavango males Unfortunately only few studies analyzed the association between androgen levels and asymmetry patterns in humans and the mechanisms through which androgens exert their influence on the development of bilateral characters remain unspecified [26,27]. On the one hand, a positive association between testosterone levels and dermatoglyphic asymmetry in males was found [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study highlighted the significance of thumbprints minutiae in assessing the level of developmental stress and instability among the Hausa population using FA. It was reported that fluctuating asymmetry is often used as a proxy to quantify developmental stressors and explore the effects of these developmental insults on individuals' health, fitness, and behavior (Benderlioglu, 2010). It may be recommended that this study be expanded to other digits and other populations in order to explore more about the pattern of the asymmetry in other digits and populations for better explanation of the phenomenon.…”
Section: Discussionmentioning
confidence: 99%